2009
DOI: 10.1080/10903120802471972
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-ResistantStaphylococcus aureuson the Stethoscopes of Emergency Medical Services Providers

Abstract: In this ED setting, MRSA was found on approximately one in three stethoscopes of EMS professionals. A longer length of time since the last stethoscope cleaning increased the odds of MRSA colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 11 publications
0
37
0
6
Order By: Relevance
“…Resultados semelhantes foram encontrados em hospitais da América do Norte, África, Oriente Médio, Índia e Reino Unido. 1,2,[5][6][7][8]15,16 Estudo realizado no Rio Grande do Sul demonstrou que a contaminação dos (50%), sendo a outra metade distribuída entre médicos preceptores, técnicos em enfermagem, médicos residentes, enfermeiros e fisioterapeutas (Tabela 1). Após a desinfecção dos estetoscópios com álcool gel, foi constatada uma redução de 71,44% da contaminação geral por microrganismos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Resultados semelhantes foram encontrados em hospitais da América do Norte, África, Oriente Médio, Índia e Reino Unido. 1,2,[5][6][7][8]15,16 Estudo realizado no Rio Grande do Sul demonstrou que a contaminação dos (50%), sendo a outra metade distribuída entre médicos preceptores, técnicos em enfermagem, médicos residentes, enfermeiros e fisioterapeutas (Tabela 1). Após a desinfecção dos estetoscópios com álcool gel, foi constatada uma redução de 71,44% da contaminação geral por microrganismos.…”
Section: Discussionunclassified
“…A ferramenta utilizada para análise foi o software Epiinfo na versão 7. [1][2][3][4] Estetoscópios contaminados já foram implicados na transmissão de bactérias patogênicas no ambiente hospitalar. [5][6][7] Apesar de simples, a frequente deficiência na limpeza dos estetoscópios pode comprometera segurança dos pacientes e do próprio profissional de saúde.…”
Section: Background and Objectivesunclassified
See 1 more Smart Citation
“…Equipment used by emergency services personnel has also been shown to have high rates of contamination. For example, 32% of stethoscopes used by emergency services personnel tested positive for MRSA [17].…”
Section: Introductionmentioning
confidence: 99%
“…Kei et al 6 study 20 different inanimate objects in an ED and found only one MRSA from the ambulance bay security door keypad. Merlin et al 17 studied 50 stethoscopes for MRSA and found 32%. Julian et al 18 sampled 123 mobile phones of veterinary teaching hospital staff.…”
mentioning
confidence: 99%